1986
DOI: 10.1159/000173992
|View full text |Cite
|
Sign up to set email alerts
|

Atypical Wenckebach Block and Concealed Conduction

Abstract: Following exercise testing, a 71 -year-old man developed atrial tachycardia with a unusual form of conduction disturbance: 4:2 atrioventricular (A-V) block. This pattern of A-V block is explainable by two different mechanisms of concealed conduction: two different levels of block in the A-V nodal region and dual A-V nodal pathways with concealed retrograde conduction of P waves. These concepts can also explain a variety of other unusual conduction disturbances.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Also, it is possible that the third and fourth ventricular beats might both have VA block and the different atrial activation sequence observed close to the third ventricular beat was caused by an impulse originating from the other ectopic focus and might be coincidental. Indeed, an atypical Wenckebach block such as a 4:2 AV block has been previously reported 36 …”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Also, it is possible that the third and fourth ventricular beats might both have VA block and the different atrial activation sequence observed close to the third ventricular beat was caused by an impulse originating from the other ectopic focus and might be coincidental. Indeed, an atypical Wenckebach block such as a 4:2 AV block has been previously reported 36 …”
Section: Discussionmentioning
confidence: 95%
“…Indeed, an atypical Wenckebach block such as a 4:2 AV block has been previously reported. 36 We have shown that different VA block patterns during AVNRT are possible and the level of retrograde VA block during AVNRT may be different in each case; however, the precise characteristics of the upper common pathway have not been fully evaluated in this study. Further studies are necessary to clarify these issues.…”
Section: Study Limitationsmentioning
confidence: 89%